Nucleotide sequence of circular DNA molecules homologues to the 240 bp tandem repeats of the intergenic spacer of Drosophila melanogaster ribosomal DNA. letter. - de Groote, F.; Renault, S.; Picard, G. (Biology of the Cell, 1990)
We have determined the nucleotide sequence of ten 240 bp repeated sequences of the DNA intergenic spacer present in circular DNA molecules purified from D melanogaster embryos. No significant difference was found with the sequence of the chromosomal units. This suggests that most of the circular molecules homologous to the 240 bp repeats are generated by homologous recombination between adjacent chromosomal units.